KARAKTERISTIK KLINIKOPATOLOGI LESI NEOPLASTIK TIROID DI RSUP SANGLAH DENPASAR BALI PERIODE 2016-2020 - Dewi, Ida Ayu Krisna Cantika; Sriwidyani, Ni Putu; Dewi, I Gusti Ayu Sri Mahendra; Winarti, Ni Wayan (Universitas Udayana, 2022)
Thyroid neoplastic lesion can be either benign or malignant/cancerous. Thyroid cancer is a type of cancer that is increasing worldwide and is the most common endocrine gland malignant in Indonesia. The purpose of this study is to determine the clinicopathological characteristics of thyroid neoplastic lesion at Sanglah General Hospital Denpasar Bali for the 2016-2020 period based on age, sex, histopathological type, and location of lesion. This research is a descriptive study with a cross sectional approach. The data used are secondary data of patients with thyroid neoplastic lesion that registered for histopathological examination at the Anatomical Pathology Laboratory of Sanglah Hospital Denpasar in 2016-2020. The data collection technique used was total sampling which result in of 407 data meeting the inclusion criteria. The results show that the most common thyroid neoplastic lesion is found in the age group of 41-50 years (25.3%), female sex (77.4%), histopathological type of papillary thyroid carcinoma (79.9%), and location of the lesion is multiple (combination of two or more locations) as much as 36.9%. The conclusions that can be drawn from this study are thyroid neoplastic lesion patients at Sanglah General Hospital Denpasar for the period 2016-2020 have the most clinicopathological characteristics aged 41-50 years, female sex, papillary thyroid carcinoma histopathology, and multiple lesion locations. The results of this study can be developed and become the basis for other research with more varied variables or other research methods such as analytical research. Keywords: Thyroid Neoplastic Lesion, Clinicopathological Characteristics, Histopathological Type